Transoral Laser Microsurgery (TLM) for Glottic Cancer: Prospective Assessment of a New Pathology Workup Protocol - Meulemans, Jeroen; Hauben, Esther; Peeperkorn, Samuel; Nuyts, Sandra; Delaere, Pierre; Vander Poorten, Vincent (Frontiers in Surgery, 2020)
Background/Purpose: The value of margin status after TLM for glottic cancer is debatable, due to difficulties in specimen orientation and margin analysis. Purpose of this study was the prospective evaluation of feasibility of a new standardized technique of oriented fixation of the TLM specimen and identification of the added value on tissue processing and margin status reporting. Methods: Patients with suspicious glottic lesions undergoing TLM were included. After resection, the specimen margins were inked in the OR using different colors. Subsequently, the specimens were fixed on a pig liver carrier and sent for further processing, accompanied with photographs of the larynx pre-TLM and of the mounted specimen. Feasibility was assessed by registration of duration of specimen preparation in the OR and the lab and by procedure-specific questionnaires. Objective evaluation included assessment of margin status and proportion of evaluable margins. Chi square tests were used to make comparisons of proportions. Results: 104 consecutive patients were included between May 2016 and September 2019. TLM was performed in a primary and salvage setting in 89.4% and 10.6% of patients respectively. Mean duration of intraoperative specimen preparation was 5.1 min (SD 2.6 min). No difficulties in orientation nor fixation during intraoperative preparation were reported in 87.5% and 88.2% respectively. Specimen orientation was judged by the pathologist as very adequate in 89.4%, with the accompanying photographs considered helpful for orientation and processing in 84.6%. Substantial difficulties in further lab processing and pathologic examination were identified in 17.7%. Deep margin evaluability was very high (98.0%) and significantly higher than the evaluability of superficial mucosal margins. Compared to our previous series published by our group (n=142), deep margin evaluability significantly rose from 62.7% to 98.0% (p=0.000) and true positive rate of the deep margins increased from 0% to 44.4% (p=0.002). Discussion/Conclusion: The new and standardized technique of oriented fixation of TLM specimens on a pig liver carrier proves feasible both in the OR and lab setting and results in high margin evaluability rates, especially for the deep margin, as well as a decreased rate of false positive deep margins when compared to a historical TLM cohort.